Diagnostic Validity Assessment of the Fifth Extended Edition of the Wechsler Intelligence Scale for Children in Students with Attention Deficit/Hyperactivity Disorder Using the Sensitivity Coefficient Method - Tavakoli, Shaghayegh; Sharifi Daramadi, Parviz; Zamanpour, Enayatollah (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to evaluate the diagnostic validity of the fifth extended version of the Wechsler Intelligence Scale for Children (WISC-V Extended) in differentiating students with Attention Deficit/Hyperactivity Disorder (ADHD) from typically developing peers using the sensitivity coefficient method.Methods and Materials: The research employed a psychometric design focusing on diagnostic validity. A total of 240 elementary school students in Tehran participated, including 120 diagnosed with ADHD (based on clinical files and educational referrals) and 120 normative students selected through simple random sampling. The WISC-V Extended, which includes five major indices—Verbal Comprehension, Visual-Spatial, Fluid Reasoning, Working Memory, and Processing Speed—was administered individually. Data analysis was conducted using the sensitivity coefficient method, comparing empirical and critical difference values across groups to determine each subtest’s ability to discriminate between ADHD and non-ADHD students.Findings: The results showed that the Verbal Comprehension subtests did not exceed critical thresholds and therefore lacked diagnostic validity. In contrast, subtests within the Visual-Spatial domain (e.g., Block Design, Visual Weights), Fluid Reasoning domain (Calculation A and B), Working Memory domain (Spatial Span Forward and Backward, Sentence Recall), and Processing Speed domain (Coding Recall, Coding Copy, Symbol Deletion) demonstrated empirical differences greater than critical values, indicating strong diagnostic sensitivity. Among these, Symbol Deletion exhibited the highest sensitivity, suggesting its specific utility in ADHD screening.Conclusion: The WISC-V Extended demonstrates partial diagnostic validity in the assessment of ADHD. While verbal subtests are more reflective of general cognitive ability, non-verbal and executive-function-oriented subtests offer stronger diagnostic differentiation. These findings underscore the importance of selective subtest interpretation for accurate ADHD identification and support the use of WISC-V Extended in clinical assessment settings.